Pentingnya Implementasi Manajemen Waktu di Dunia Konstruksi - Irika Widiasanti; Adriyan Rama Musti; Alwan Izzudin Rabitsani; Budi Afriani; Muhammad Ilham Ardiansyah; Nadia Seftiani (Universitas Batanghari Jambi, 2023)
Work completion time is one of the main factors of successful implementation in a construction project. A job that experiences delays in completion on a project will greatly impact the budget that has been planned before. Not only in cash flow but can also result in unwanted cost overruns. Time management is an essential part of any project activity, where time is one of the resources for work that must be managed properly and efficiently. The potential for waste and project failure will be more likely to occur without good time management. Therefore, there is a need for time management on well-managed projects. In this study, we will discuss how time management in the project, what important things are in time management on the project and investigate what obstacles are often encountered in project control. The method used in this study is qualitative research methods with descriptive analysis techniques and using library research. The result of this study is that we can find out what are the scopes in time management on projects, where the discussion refers to PMBOK (Project Management Body of Knowledge).